2017
DOI: 10.5935/2318-7670.v05n04a12
|View full text |Cite
|
Sign up to set email alerts
|

Variables Influencing Working Time and Skidder Productivity in Wood Extraction

Abstract: The effects of certain operational variables on working time and skidder productivity in wood extraction in Eucalyptus grandis stands were investigated in this research. The study was conducted at a forestry plantation located in the municipality of Telêmaco Borba, Paraná State. Through a time and motion study the operational cycle time, mechanical availability, operational efficiency and productivity in relation to the variables volume, cycle time and extraction distance were quantified. The data were analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…The search activities and loading and unloading of this research consumed less time of the operating cycle time. According to Sandhu (2008) and Lopes et al (2017), skidder occupies the longer in active form, i.e. performing the operations of empty and loaded displacement, and therefore consuming less proportional cycle time in loading and unloading, corroborating the results of this research.…”
Section: Average Effective Timesupporting
confidence: 83%
“…The search activities and loading and unloading of this research consumed less time of the operating cycle time. According to Sandhu (2008) and Lopes et al (2017), skidder occupies the longer in active form, i.e. performing the operations of empty and loaded displacement, and therefore consuming less proportional cycle time in loading and unloading, corroborating the results of this research.…”
Section: Average Effective Timesupporting
confidence: 83%
“…Regarding the machine elements, the loading and unloading of wood logs, which represented 17.7% of the grapple skidder's operational cycle time, indicated that the size of the stands did not influence these parameters. Lopes et al [47], Diniz et al [74], Naderializadeh and Crowe [75], and Ross et al [76] add that most of the operational cycle of this machine occurs actively, that is, is spent on activities associated with the greatest driving force of self-propelled forest machines. The optimization of the dimensioning of the stands in the forest areas is intended to adapt them to the management units, to facilitate silvicultural activities, fire prevention, and combat, and to minimize the operational cycle times of wood-harvesting activities.…”
Section: Discussionmentioning
confidence: 99%
“…The operational efficiency of the grapple skidder (Equation ( 2)) allowed us to express the percentage of time effectively worked in relation to the total time programmed [47].…”
Section: Technical and Economic Analysis Of Wood Extractionmentioning
confidence: 99%
“…The lower maintenance cost of the skidder can be explained by the machine's characteristics which has a closed hydraulic system, with greater protection of the hoses and greater robustness. Lopes et al (2017) also points out that this machine consumes longer operational cycle time in displacement, reducing exposure to trunks and branches, unlike what normally occurs with the feller buncher and harvester.…”
Section: Discussionmentioning
confidence: 99%